2007 Proceedings 57th Electronic Components and Technology Conference 2007
DOI: 10.1109/ectc.2007.373778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PCB Surface Finish and Thermal and Temperature/Humidity Aging on the Performance of a Novel Anisotropic Conductive Adhesive for Lead-free Surface Mount Assembly

Abstract: The electronics industry, in recent years, has been focusing primarily on product miniaturization and lead-free assembly. The need to eliminate lead-based materials as a means of interconnection has renewed the industry's interest in exploring other means of assembling surface mount devices reliably, especially using conductive adhesives. This paper will discuss the performance characteristics and research findings pertaining to a novel anisotropic conductive adhesive for lead-free electronics packaging applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…129 Different surface finishes result in a wide range of surface roughness of the electrodes, for example as low as a few nm in the electrodeposited Sn method 130 and as high as a few hundred nm in the immersion Sn. 131 Surface roughness of electrodes affects the electrolyte formation step. 17,132,133 A rougher surface contains more localized regions for water adsorption, for example, pores, pits, and scratches.…”
Section: Surface Conditionsmentioning
confidence: 99%
“…129 Different surface finishes result in a wide range of surface roughness of the electrodes, for example as low as a few nm in the electrodeposited Sn method 130 and as high as a few hundred nm in the immersion Sn. 131 Surface roughness of electrodes affects the electrolyte formation step. 17,132,133 A rougher surface contains more localized regions for water adsorption, for example, pores, pits, and scratches.…”
Section: Surface Conditionsmentioning
confidence: 99%
“…Indirectly, the polished surface minimizes air gaps and increases the contact surface area as the purpose of thermal paste as thermal interface material. From Table I, it is observed that the R thJA value reduced by 0.63 K/W for polished surface with thermal paste condition (Ramkumar and Srihari, 2007). From these observations, noticeable reduction in R thJA value could be observed for thermal paste condition on polished surface than the rough surface.…”
Section: Thermal Transient Analysismentioning
confidence: 72%
“…A conventional way of evaluating the robustness of this type of interconnects is e.g. by an accelerated humidity test at 85°C/85%RH for 500 to 2000 hours [1,2,3,4,5,6]. The long test duration, however, determines to a large extend the throughput time for new developments.…”
Section: Introductionmentioning
confidence: 99%